(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: 1-To study the clinical presentation of infected pseudoaneurysm of lower limb in I. V drug abusers. 2-To evaluate the surgical treatment and its outcome. Methods: Patients presenting with signs and symptoms of infected pseudoaneurysms in surgical -3 were studied. The diagnosis of the disease was made with history of intravenous drug abuse and clinical examinations. The parameters studied were demographic aspects, clinical presentation, investigations, surgical management, postoperative complications and follow up. The clinical data was saved in a computer Performa and was analyzed. Results: Fifteen patients of infected aneurysm of lower limb were managed from January 2006 to December 2012. All were male and median age was 28 years. Ten patients had pseudoanurysm in left groin, two in right groin and one had in left popliteal fossa and two patients had aneurysm in both right and left groins and in polpliteal fossa. In 8 patients, reason of coming to hospital was hemorrhage, in 2 patients reason of admission was high grade fever, 4patient presented with an ulcerated, non healing pulsatile wound. One patient was brought by his family for the management of addiction. On examination, there was severe sepsis with abscess, necrosis and extensive cellulitis in 5 patients. Five patients had involvement of both common femoral and superficial femoral artery. In two patients common femoral artery was involved alone, two had popliteal artery involvement. In 6 patient involvements of femoral artery and external iliac vessels was noted. Proximal and distal ligation of the infected aneurysm with excision was done in all cases. In two patient reversed saphenous vein graft was attempted without success. No patient needed postoperative amputation in the recorded follow up. Five patients had postoperative follow up for 7 months, 3 patients for 2months without any complaint of intermittent claudication. Conclusion: The infected pseudoaneurysm of lower limb is a life threatening illness of young male I.V drug abusers. Ligation and excision of infected pseudoaneurysm is a safe surgical management to save limb and life of the patient. Long term rigorous follow up is required to note delayed postoperative outcome.